Patent Pledges in The Automotive Industry A multiple case-study on the reception and attitudes to patent pledges - Slettengren, Emanuel; Wenger, Lukas (My University, 2023)
Patent pledges can be defined as voluntary commitments by a patent holder to limit the enforcement of their patents made to the public or at least to large segments of specific markets. Recently, they have gained attention in relation to the Covid-19 pandemic, where several companies made such an initiative in a number of industries. While patent pledges have existed for more than 20 years, the concept has seen relatively little research. Specifically, no research exists which investigates the impact of pledges on a full industry, how they are received and perceived by actors in it, and what factors may influence adoption decision-making in different ways. The purpose of this thesis is to investigate the concept of patent pledges within the context of the automotive industry. Specifically, it seeks to investigate the concept from the perspective of the pledgee (the receiving party) and assess how potential pledgees in the industry receive and perceive both the concept on a general level, and the pledges already existing in the industry. The project was designed as a multiple case study based upon three identified patent pledges in the automotive industry. The data was collected through semi-structured interviews with IP-professionals in the industry. The study resulted in identifying several different characteristics and designs of current pledges in the industry, and some recommendations for future taxonomies of patent pledges. Specifically, the results indicate that the manner in which a pledge is adopted greatly differentiates the pledges from each other and how they are received. Three patent pledges with different pledge designs were identified, by Tesla, Ford and Toyota. The results indicate that successful pledges must achieve a suitable balance between simplicity and clarity which current pledges were not found to do. It was also found that actors in the automotive industry have a predominantly negative attitude towards both patent pledges in general and towards the existing pledges. Furthermore they do not think that the pledges have had an impact on the industry. The perceived motivations behind the pledges under study differed significantly from previous more general studies, trending towards motives which may be understood as less altruistic. The study also found that characteristics of the specific Technology as well as how the Adoption process works are the most important factors which actors assess in the adoption process. The results also suggest that some factors, such as Pricing and the External Environment, may be less important for such decisions than previous theory may indicate